1982
DOI: 10.1002/dev.420150108
|View full text |Cite
|
Sign up to set email alerts
|

Early social deprivation and the ontogeny of unrestricted social behavior in the laboratory rat

Abstract: The unrestricted adult social and nonsocial behavior of albino rats isolated from 21 to 70 days of age was compared with the behavior of rats receiving normal social experience. Isolated animals exhibited aberrant self-manipulative behaviors during the period of isolation, and both isolate-reared males and females were more aggressive than their group-reared counterparts. The hypothesis that females are buffered against the effects of social isolation received little support. Numerous gender differences and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…More generalized disruptions of sexual behavior also have been reported (Duffy & Hendricks, 1973;Gerall, Ward, & Gerall, 1967). Rats raised in social isolation during the play period have been reported to be more aggressive (Byrd & Briner, 1999;Day, Seay, Hale, & Hendricks, 1982), even against members of different species (Johnson, DeSisto, & Koenig, 1972;but see Portegal & Einon, 1989). In a careful analysis of the effects of social isolation during the play period, rats were found to have an impaired ability to address social challenges such as social defeat, but to behave normally in facing nonsocial challenges such as open-field tests and plus-maze learning (van den Berg, Hol, et al, 1999).…”
mentioning
confidence: 90%
“…More generalized disruptions of sexual behavior also have been reported (Duffy & Hendricks, 1973;Gerall, Ward, & Gerall, 1967). Rats raised in social isolation during the play period have been reported to be more aggressive (Byrd & Briner, 1999;Day, Seay, Hale, & Hendricks, 1982), even against members of different species (Johnson, DeSisto, & Koenig, 1972;but see Portegal & Einon, 1989). In a careful analysis of the effects of social isolation during the play period, rats were found to have an impaired ability to address social challenges such as social defeat, but to behave normally in facing nonsocial challenges such as open-field tests and plus-maze learning (van den Berg, Hol, et al, 1999).…”
mentioning
confidence: 90%
“…For example, although isolation rearing disrupts male sexual behavior, it has little effect on fema1e sexual behavior (Duffy & Hendricks, 1973;Hansen, 1977). Isolation rearing does, however, increase aggression, reduce affiliative behavior, and increase open field activity in female as weIl as male rats (Dalrymple-Alford & Benton, 1981;Day et al, 1982).…”
mentioning
confidence: 99%
“…One explanation for this phenomenon is that post-weaning individual housing might cause alteration in the recognition of social cues from sexually receptive female rats. Increased aggression is one of the most well-known abnormal male–male social interactions observed in adult male rats housed individually after weaning [5]. An earlier study demonstrated that post-weaning individual housing might not only increase the level of aggressiveness, but also might result in abnormal attack patterns and deficits in social communication in adult male rats [17].…”
Section: Discussionmentioning
confidence: 99%
“…Post-weaning individual housing induces significant alterations in social behaviors of laboratory rats compared with socially housed (i.e., group-housed) rats [1, 3, 5,6,7, 15, 20, 21]. Our previous study showed that adult male rats that were housed individually after weaning emitted fewer ultrasonic vocalizations referred to as “50-kHz calls” compared with rats housed socially after weaning that encountered sexually receptive female rats [11].…”
Section: Introductionmentioning
confidence: 99%